2020
DOI: 10.47717/turkjsurg.2020.4744
|View full text |Cite
|
Sign up to set email alerts
|

The effect of postoperative serratus anterior plane block on postoperative analgesia in patients undergoing breast surgery

Abstract: Objective: This study aimed to evaluate the effect of serratus anterior plane block (SAP) on postoperative morphine consumption. We aimed to determine the differences between both similar blocks and evaluate the effect of the methods of application of this block on patients' postoperative pain scores and morphine consumption. Material and Methods:This study is a single-center, prospective and observational study performed with 40 volunteer patients with American Society of Anesthesiologists (ASA) I-III, who we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…The years of publication of these studies ranged from 2017 to 2021, and the sample size ranged from 40 to 116. Overall, 7 trials, 5 trials, and 1 trial used bupivacaine [ 26 , 27 , 30 , 32 , 34 , 36 ], ropivacaine [ 12 , 29 , 33 , 35 , 37 ], and levobupivacaine [ 28 ] as a local anaesthetic, respectively. The volume of the local anaesthetic was 20–40 mL, and its concentration was 0.25%–0.5%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The years of publication of these studies ranged from 2017 to 2021, and the sample size ranged from 40 to 116. Overall, 7 trials, 5 trials, and 1 trial used bupivacaine [ 26 , 27 , 30 , 32 , 34 , 36 ], ropivacaine [ 12 , 29 , 33 , 35 , 37 ], and levobupivacaine [ 28 ] as a local anaesthetic, respectively. The volume of the local anaesthetic was 20–40 mL, and its concentration was 0.25%–0.5%.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 10 trials used the random sequence generation method [ 12 , 27 37 ], 9 trials explained the allocation concealment [ 12 , 26 , 28 , 30 , 33 , 35 , 36 ], 3 trials explicitly described the method of double blinding [ 12 , 28 , 36 ], and 9 trials described blinded assessors and evaluated attrition bias [ 12 , 27 , 28 , 31 , 33 37 ]. There was no selective reporting.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of participant and personnel blinding, 3 studies were not blinded [30,34,50], and 13 were not described [4, 16, 32, 37-42, 44, 45, 49, 52]. Among the result-blinding methods, one item was not blinded [49], and 7 studies did not specify whether they have blinded [16,30,32,38,45,47,49]. All studies were not selectively reported.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…Nineteen studies reported 24 h postoperative opioid consumption in patients undergoing thoracic or breast surgery [5,15,16,32,33,[36][37][38][45][46][47][48]. Meta-analysis showed that SAPB significantly reduced 24 h postoperative opioid consumption compared with the control group (Figure 8) (SMD, −2.77; 95% CI, −3.56 to −1.97; P < 0.01; I 2 = 97%).…”
Section: Postoperative Opioid Consumption At Hmentioning
confidence: 99%
See 1 more Smart Citation